(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
The article is devoted to the application of deformation preventing measures for dams constructed out of swelling soils. Laboratory and fields tests have shown the relation between swelling pressure-compaction tension has a nonlinear character. On the basis of received dependence it is proposed to compensate the swelling pressure by the load calculated with the formula h = 0,3 σsw /ρ, where ρ is a soil density, σsw is a swelling pressure.